Gas Slug Compound Flooding in Low and Ultra-low Permeability Layer. Issue 1 (February 2021) - Chen, Taoping; Sun, Wen; Bi, Jiaqi; Zhao, Bin; He, Ru
Abstract: In order to improve the recovery of gas slug compound flooding in low permeability and ultra-low permeability reservoirs, two methods of the carbon dioxide-nitrogen and the rich gas-nitrogen compound flooding are studied. The results show that in low permeability and ultra-low permeability reservoirs, the use of a single injection of a reasonable pre-slug(carbon dioxide or rich gas) + subsequent nitrogen slug compound flooding can reduce the size of the pre-slug, give full play to the advantages of both the pre-slug and nitrogen, and obtain a better flooding efficiency. Under the same conditions, the recovery of the ultra-low permeability cores used in this experiment is 7.6% higher than the recovery of the low permeability cores on average. However, since the reasonable size of the rich gas pre-slug is 0.6 PV, twice as much as the reasonable size of the carbon dioxide pre-slug, and the price of unit volume of the rich gas slug is 1.82 times as much as the price of the carbon dioxide slug under the condition of injection, the final input-output ratio of the carbon dioxide-nitrogen compound flooding is 2.0∼2.69 times as much as that of the rich gas-nitrogen compound flooding.